Making a personal difference:communications in healthcare - Nichols, Bill (Mednarodno inovativno poslovanje, 2019)
Innovation happens all around the Universe and is a fundamental mechanism of evolution. Living creatures cannot but exist and develop through innovation. Innovation happens through mutations that make sense in retrospect only. Natural selection makes certain mutations as beneficial and other as something that was already forgotten. As much as genes serve as quantized smaller units where innovation takes place in physical bodies, memes serve as basic quantized units of human culture. Memes as second replicators to genes obey similar laws of evolution and thus innovation as genes. Innovation can be propagated only by removing obstacles on one side and by allowing mutations to emerge as long as they do not destroy identity.
Keywords: communications; education; health; health behaviour; izobraževanje; komuniciranje; zdravje; zdravstveno vedenje